2021
DOI: 10.1186/s12889-021-11945-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of public health interventions during the first epidemic wave of COVID-19 in Cyprus: a modelling study

Abstract: Background Cyprus addressed the first wave of SARS CoV-2 (COVID-19) by implementing non-pharmaceutical interventions (NPIs). The aims of this study were: a) to estimate epidemiological parameters of this wave including infection attack ratio, infection fatality ratio, and case ascertainment ratio, b) to assess the impact of public health interventions and examine what would have happened if those interventions had not been implemented. Methods A dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…HCI and age variables: the coupled effect of health care system and elderly According to the literature, the health care system was considered by means of different indicators such as ICU level [11], Prevention and Control (P&C) capacity [71], the number of hospitals and the 4 T's (tracing, tracking, testing and treating) [69]. In this work, and as previously introduced, HCI index was adopted as a public health policy indicator.…”
Section: Benchmark Studymentioning
confidence: 99%
See 2 more Smart Citations
“…HCI and age variables: the coupled effect of health care system and elderly According to the literature, the health care system was considered by means of different indicators such as ICU level [11], Prevention and Control (P&C) capacity [71], the number of hospitals and the 4 T's (tracing, tracking, testing and treating) [69]. In this work, and as previously introduced, HCI index was adopted as a public health policy indicator.…”
Section: Benchmark Studymentioning
confidence: 99%
“…The results of the corresponding simulations showed that the low temperature could allow the proliferation of the viruses but also temperature may cause host shifts (denoted as temperature anomalies) for viruses and increases the susceptibility of more susceptible species. Nevertheless, after including HDI in the models, the environmental factors lost their effects and x x [11] x d x e [15] x [16] x [18] x d [51] x [52] x [53] x [54] x [55] x [56] x [57] x x [58] x [59] x [60] x [61] x…”
Section: Benchmark Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As the COVID-19 vaccine campaign was not launched in mainland China until early 2021, non-pharmaceutical interventions (NPIs) remained the main way to control the second-wave of COVID-19. The effects of NPIs on controlling COVID-19 transmission have been widely confirmed in the first-and second-wave [8][9][10][11][12]. A study from Italy by Manica et al [13] has estimated that the three-tiered restriction system, which was taken by Italian government to counter the national second-wave, effectively lowered the reproduction number below 1 in 85 out of 107 provinces.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [17][18][19][20][21][22][23] reported population-level covariates for predicting excess deaths in a community. Some of the factors that have been found to be significantly associated include urbanicity; population density; proportion of elderly in the population; presence of specific comorbidities; health system and governance indicators like human resource or bed density; coverage of public health interventions; and indicators of severity of the pandemic.…”
mentioning
confidence: 99%